Analysis of Learning Needs for Cell Biology: a Study From the Perspectives of Lecturers and Students in Palangka Raya City - Hasanah, Muqor Rama; Zannah, Fathul; Aufa, Mohamad Nor; Nurkhaliza, Gusti Nida; Imelda; Fenny (Bioilmi: Jurnal Pendidikan, 2025)
Cell Biology education at the university level, including in Palangka Raya City, continues to face significant challenges due to the abstract and complex nature of the subject matter. The predominant reliance on conventional teaching methods—such as lectures and static visual aids has proven inadequate in supporting students’ conceptual understanding. This study aims to analyze the learning needs of Cell Biology from the perspectives of both lecturers and students to formulate more adaptive and innovative instructional strategies. A descriptive qualitative approach with a mixed-methods design was employed, involving 9 lecturers and 120 undergraduate students from three higher education institutions in Palangka Raya: Universitas Palangka Raya, Universitas Muhammadiyah Palangkaraya, and IAIN Palangka Raya. Data were collected through questionnaires, semi-structured interviews, and document analysis. The results showed that 72% of students found Cell Biology difficult, particularly on topics such as cellular respiration, membrane transport, and organelle interactions. Most students reported a lack of interactive learning media, while lecturers acknowledged the need for training in the integration of educational technologies. A comparative analysis revealed a clear gap between lecturers’ focus on content delivery and students’ expectations for contextual and visually rich learning experiences. The findings underscore the urgent need to develop technology-enhanced learning strategies such as 3D media, AR/VR tools and to strengthen institutional support to improve Cell Biology education in the local context of Central Kalimantan.